Evaluation of strength and conditioning changes during a Division II collegiate softball season - Thompson, K, J.; Barkley, S. A. (Journal of Fitness Research, 2013)
Female participation in athletics, including intercollegiate athletic participation, has grown greatly in a variety of sports throughout the past two decades (Marques et al., 2008). With this higher level of participation has come an increase in supervised strength and conditioning programs and a goal of preparing female student-athletes to perform at their maximal potential throughout the course of a competitive season. As strength and conditioning coaches work to help the athletes improve in power, explosiveness, endurance and strength, they must also be aware of the unique goals and circumstances particular to specific sports (Nimphius et al., 2010).